TRADISI SEDEKAH LAUT DI WONOKERTO KABUPATEN PEKALONGAN: KAJIAN PERUBAHAN BENTUK DAN FUNGSI (JPP, 2011)
The tradition of alms in the village of Wonokerto sea Regency Pekalongan is a form ofcultural offerings to the sea conducted in Sura society. Over time the development ofform and function of marine alms to experience growth and change because of the effectsocio cultural changes in society. The purpose of marine research charity in Wonokertodone to clarify and describe the changes in the form of alms the sea, the sea change incharity functions related to social life and the role of culture in the educational charity forthe people of the sea. The results and discussion show that the tradition of the sea donationform and function changes caused by social change Wonokerto culture. Changes includethe time and place of execution, and the aspects of offering support. As for changesin the functions of the ritual evolved into a spiritual function, the function of entertainment,communication function, the function of cultural preservation, educational functionsand economic functions. Changes in form and function of marine charity has a rolein education for the community values education that is noble race, education, spirituality,education, work ethos, culture and education conservation of natural environments.Changes in form and function of marine charity tradition influenced by changes in socialculture, including changes to the system of science,technology,and economic systems.Keywords: form, function, community education,change